The interpretive dimensions of the conceptual metaphor theory in digital art and its role in enriching the aesthetic values ​​of the learner (Journal of the College of Basic Education, 2022)
An analytical study of four chapters, the first chapter was based on a research problem that focused on conceptual metaphor as a means of cultural communication and relationships associated with Balzhn intellectual and speculative, which provides the receiver (the learner). And exploring the conceptual metaphor that has evolved at the hands of both "George Wyckoff and Mark Johnson, the theory of" embodied dimensional interpretive metaphor conceptual art as a formative language influenced by technological development, which is of the concepts of the culture of the picture, it is impossible to talk about the metaphor in art's isolation from the image processing software; digital screens and others. This means that current research studying the interpretive dimensions of conceptual metaphor in digital art in an attempt to uncover the aspects of the relationship between them; and to explore their role in enriching the aesthetic values ​​of the learner. In order to shed light on the problem of this research, it has drawn up (the researcher) the following of questions: Are the conceptual metaphor for the role in strengthening the creative-oriented digital art? Did dimensions interpretive theory of conceptual metaphor in digital art role in enriching the aesthetic values ​​of the learner? The aim of the research disclosure deportation interpretive theory of conceptual metaphor in digital art and its role in enriching the aesthetic values ​​of the learner. The third chapter included a description of the framework of the procedural and the most important educational applications based on the metaphor conceptual to search through the first two readings: the analysis of metaphor conceptual digital art and how one interacts with the other, and the second interpretation of metaphor conceptual digital art and its role in enriching the aesthetic values ​​of the learner mechanisms. And it resulted in the search results that the semantics of the metaphor and the dimensions of intellectual bind antibodies reveal suggestive ability diagnosed idea of ​​substitution between his nickname, and the nickname of him. As well as metaphors of digital art has become more shorthand, purpose artistic experience where references Alastarah formal vocabulary for simulating reality is different. And concluded (the researcher) discussed a number of recommendations proposals.